Kalevala in international masks: a Japanese Aino and Kalevala dell’arte. - Kendra Willson (Brill, 2022)
Stories from Finnish mythology (most often mediated through Elias Lonnröth's Kalevala) have been adapted for the stage in myriad ways which synthesize them different international traditions. Aleksis Kivi's Kullervo (1860) drew strongly on the tradition of Greek tragedy. Some modern productions synthesize Kalevala stories with formal dramatic traditions from other parts of the world. Two recent examples are Kalevala dell'arte (2010) (directors and dramaturgs Soile Mäkelä and Davide Giovanzana) and Aki Suzuki's Aino - Kalevala - Planet Earth No. 3 (2013). Aino presents the story of Joukahainen and Aino in the tradition of Japanese Noh theater. Kalevala dell'arte uses the language of the 16th c. Italian commedia dell'arte tradition (as revived in the 20th c. by Jacques LeCoq). The archetypes and formal techniques of these international traditions lend additional dimensions to the Kalevala stories and characters. The martial language of Aino brings out the nature of the poetic duel between Väinämöinen and Jokahainen as a stylized battle. The commedia dell'arte techniques used in Kalevala dell'arte emphasize physicality and provide means of exploring status, gender and transformation. The dynamism of both the Kalevala myths and the traditional theatrical forms is seen in these contemporary, international fusions.
Northern myths, modern identities: the nationalisation of northern mythologies since 1800